Prediksi Parameter Kelembapan Udara Berdasarkan Data Penyinaran Matahari Menggunakan Metode Aproksimasi Kuadrat Terkecil - Purnama, Prasanti Mia; Fadila, Nadia; Baharsyah, Najmi Fajrin; Farahnas, Ulya; Hasanah, Mauilal (Zeta - Math Journal, 2023)
Humidity is the measure, generally expressed as a percentage, of water vapor that presents in the air. Each place has different percentage of humidity. It happens since humidity is affected by solar radiation intensity. In this study, the percentage of relative humidity is being predicted by applying least square method and Gauss elimination. The data used in this research is the data of relative humiditity and solar radiation intensity during 2018 until 2022 which have been collected by Trunojoyo Stationary of Meteorology. The result shows that the approximation function generated by linear square method is powerful enough in order to predict the relative humidty, based on the relatively small error accumulated.